ANALYSIS OF THE APPLICATION OF “THE MISSING BABIES ACT” - Arsenijević, Bojana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The Act on Establishing the Facts about the Status of Newborn Children who are Suspected of Having Disappeared from the Maternity Hospitals in the Republic of Serbia, colloquially known as the Missing Babies Act, was adopted in 2020. The paper presents pioneering analysis of the results of the Act’s application. The empirical research included the practice of the high courts in Niš, Kragujevac, Belgrade and Novi Sad. By using the statistical and the random sample methods, the Author reflects on the first results of the application of the Act. The act regulates the procedure for determining the facts regarding the status of the “missing babies” and awarding compensation for non-pecuniary damages. It was adopted with two stated goals. The first goal was to finally solve the problem of unreliable information on the status of babies who are suspected of being missing and to award compensation for non-pecuniary damages to persons whose right to respect for family life was violated. The second goal was to fulfill the obligations from the judgment of the European Court of Human Rights in the case of Jovanović v. Serbia (appl.12794/08). The short six-months deadline to initiate the procedure for determining the facts about the status of the “missing babies”, its preclusive nature, and the ruling principle of urgency when conducting these proceedings should have indicated the importance given to resolving the issue of “missing babies”. The preview of the results of the application of the Act has shown that the Act did not achieve its aims.